'Natural' Breastfeeding in Comparative Perspective: Feminism, Morality, and Adaptive Accountability. Issue 1 (1st January 2017) - Faircloth, Charlotte
ABSTRACT: Based on research in London and Paris with mothers from an international breastfeeding support organisation, this paper explores the narratives of women who breastfeed their children 'to full term' (typically for a period of several years) as part of a philosophy of 'attachment parenting'. In line with wider cultural trends (in the UK, at least), one of the most prominent 'accountability strategies' used by this group of mothers to explain their full-term breastfeeding is the claim that this is 'most natural', drawing on an evolutionary 'hominid blueprint' of care, as well as an ecological perspective on social life more broadly. What follows in the paper is a reflection on how notions of 'natural' parenting are given credence in narratives of mothering, and how this is used adaptively in local contexts as part of women's 'identity work'. If in the UK the 'natural' is used as a moral grounding for action, the same cannot be said for women in France. Using a comparative perspective, the argument is that this reflects very different trajectories within the feminist movement in the UK and France. Where in certain mileux in the UK it is considered desirable, even mandatory, to 'get in touch with' nature, in France, it is considered something to escape, subordinate, and resist. Far from being 'flattened', then, the purchase of nature as it relates to moral negotiations of mothering appears to be stronger than ever. 1